Nicotine dependence as a moderator of a quitline-based message framing intervention. - Fucito, Lisa M; Latimer, Amy E; Carlin-Menter, Shannon; Salovey, Peter; Cummings, K Michael; Makuch, Robert W; Toll, Benjamin A (Drug and alcohol dependence, 2011)
High nicotine dependence is a reliable predictor of difficulty quitting smoking and remaining smoke-free. Evidence also suggests that the effectiveness of various smoking cessation treatments may vary by nicotine dependence level. Nicotine dependence, as assessed by Heaviness of Smoking Index baseline total scores, was evaluated as a potential moderator of a message-framing intervention provided through the New York State Smokers' Quitline (free telephone based service). Smokers were exposed to either gain-framed (n=810) or standard-care (n=1222) counseling and printed materials. Those smoking 10 or more cigarettes per day and medically eligible were also offered a free 2-week supply of nicotine patches, gum, or lozenge. Smokers were contacted for follow-up interviews at 3 months by an independent survey group. There was no interaction of nicotine dependence scores and message condition on the likelihood of achieving 7-day point prevalence smoking abstinence at the 3-month follow-up contact. Among continuing smokers at the 3-month follow-up, smokers who reported higher nicotine dependence scores were more likely to report smoking more cigarettes per day and this effect was greater in response to standard-care messages than gain-framed messages. Smokers with higher dependence scores who received standard-care messages also were less likely to report use of nicotine medications compared with less dependent smokers, while there was no difference in those who received gain-framed messages. These findings lend support to prior research demonstrating nicotine dependence heterogeneity in response to message framing interventions and suggest that gain-framed messages may result in less variable smoking outcomes than standard-care messages.
Keywords: Adult; Counseling; Female; Follow-Up Studies; Hotlines; Humans; Male; Middle Aged; Smoking Cessation; Tobacco Use Disorder